The Space-to-Product Ratio Effect: How Interstitial Space Influences Product Aesthetic Appeal, Store Perceptions, and Product Preference - Sevilla, Julio; Townsend, Claudia (Journal of Marketing Research, 2016)
The authors identify and examine the effect of space-to-product ratio on consumer response; very generally, consumers perceive products as more valuable when more space is devoted to their display. In both lab and field studies, the authors find that this phenomenon influences total sales, purchase likelihood, and even perceived product experience (taste perceptions). More interstitial space increases perceptions of individual products as more aesthetically pleasing and the store as more prestigious. The authors find these effects across a variety of product categories and rule out a number of competing alternative explanations that are based on perceptions of product popularity, scarcity, assortment search difficulty, and messiness.